Protective interplay: Mycobacterium tuberculosis diminishes SARS-CoV-2 severity through innate immune priming - Williams, Brittany D.; Ferede, Debora; Abdelaal, Hazem F. M.; Berube, Bryan J.; Podell, Brendan K.; Larsen, Sasha E.; Baldwin, Susan L.; Coler, Rhea N. (Frontiers in Immunology, 2024)
At the beginning of the COVID-19 pandemic those with underlying chronic lung conditions, including tuberculosis (TB), were hypothesized to be at higher risk of severe COVID-19 disease. However, there is inconclusive clinical and preclinical data to confirm the specific risk SARS-CoV-2 poses for the millions of individuals infected with Mycobacterium tuberculosis (M.tb). We and others have found that compared to singly infected mice, mice co-infected with M.tb and SARS-CoV-2 leads to reduced SARS-CoV-2 severity compared to mice infected with SARS-CoV-2 alone. Consequently, there is a large interest in identifying the molecular mechanisms responsible for the reduced SARS-CoV-2 infection severity observed in M.tb and SARS-CoV-2 co-infection. To address this, we conducted a comprehensive characterization of a co-infection model and performed mechanistic in vitro modeling to dynamically assess how the innate immune response induced by M.tb restricts viral replication. Our study has successfully identified several cytokines that induce the upregulation of anti-viral genes in lung epithelial cells, thereby providing protection prior to challenge with SARS-CoV-2. In conclusion, our study offers a comprehensive understanding of the key pathways induced by an existing bacterial infection that effectively restricts SARS-CoV-2 activity and identifies candidate therapeutic targets for SARS-CoV-2 infection.